1993
DOI: 10.1002/fut.3990130802
|View full text |Cite
|
Sign up to set email alerts
|

Hedge ratios and basis behavior: An intuitive insight?

Abstract: onsiderable work has been devoted to the question of the proper volume of futures c contracts needed to protect or enhance the value of a given on-hand or anticipated volume of a physical commodity until the time of the commodity's final disposal in the cash market [Blank (1989);Kahl (1983);Witt et al. (1987)l.The purpose of this article is to examine the practical meaning and use of elemental hedge ratios derived from the simple regression of end-of-hedge cash and futures price levels and, alternatively, pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
1
0
3
Order By: Relevance
“…Shafer (1993) noted thai the "full" portfolio model is generally not nppropriate because hedging as practiced is essentially either (I) an attempt at arbitrage via Working's anticipated change in relative prices (basis change) and/or (2) a zero return process where the objective is a minimum risk bearing price relative to some break-even price, probably in an anticipatory hedge. Hartz murk ( 1988) has suggested that even large commercial firms are generally risk minimizers rather than "nimble footed speculators" reacting to expected price changes.…”
Section: Wenling Yang Page25mentioning
confidence: 99%
“…Shafer (1993) noted thai the "full" portfolio model is generally not nppropriate because hedging as practiced is essentially either (I) an attempt at arbitrage via Working's anticipated change in relative prices (basis change) and/or (2) a zero return process where the objective is a minimum risk bearing price relative to some break-even price, probably in an anticipatory hedge. Hartz murk ( 1988) has suggested that even large commercial firms are generally risk minimizers rather than "nimble footed speculators" reacting to expected price changes.…”
Section: Wenling Yang Page25mentioning
confidence: 99%
“…Je negativer der Bias wird, umso höher ist die für den Risikotransfer zu entrichtende Risikoprämie für einen Long-Hedger ( eine Terminkaufposition zu Hedgingzwecken).109 Eine Grenzwertbildung eines beliebigen Risikoaversionskoeffizienten A; gegen Null zeigt, daß o zu Null wird 110. Das Ergebnis kommt nur zustande, weil Transaktionskosten unberücksichtigt bleiben 111. Das Modell vermittelt insbesondere durch die Annahme rationaler Erwartungen den Eindruck, daßEvamaria Wagner -978-3-631-75600-3 Downloaded from PubFactory at 09/22/2020 05:32:54AM via free access…”
unclassified
“…Também são bastante difundidos testes como o de Ljung-Box e o teste dos multiplicadores de Lagrange para captar a presença de efeitos GARCH. Esses últimos são feitos através de um teste t para a variável TR 2 , onde T é o número de observações e R 2 é o coeficiente que indica o grau de ajustamento para o seguinte modelo: (65) o teste é feito sob a hipótese nula de que a variância condicional é constante.…”
Section: Ldentijicaçâo Dos Modelosunclassified